Formation of an artificial Mg2+-permeable interphase on Mg anodes compatible with ether and carbonate electrolytes - Li, Y; Zuo, P; Li, R; Huo, H; Ma, Y; Du, C; Gao, Y; Yin, G; Weatherup, RS (American Chemical Society, 2021)
Rechargeable Mg-ion batteries typically suffer from either rapid passivation of the Mg anode or severe corrosion of the current collectors by halogens within the electrolyte, limiting their practical implementation. Here, we demonstrate the broadly applicable strategy of forming an artificial solid electrolyte interphase (a-SEI) layer on Mg to address these challenges. The a-SEI layer is formed by simply soaking Mg foil in a tetraethylene glycol dimethyl ether solution containing LiTFSI and AlCl3, with Fourier transform infrared and ultraviolet–visible spectroscopy measurements revealing spontaneous reaction with the Mg foil. The a-SEI is found to mitigate Mg passivation in Mg(TFSI)2/DME electrolytes with symmetric cells exhibiting overpotentials that are 2 V lower compared to when the a-SEI is not present. This approach is extended to Mg(ClO4)2/DME and Mg(TFSI)2/PC electrolytes to achieve reversible Mg plating and stripping, which is not achieved with bare electrodes. The interfacial resistance of the cells with a-SEI protected Mg is found to be two orders of magnitude lower than that with bare Mg in all three of the electrolytes, indicating the formation of an effective Mg-ion transporting interfacial structure. X-ray absorption and photoemission spectroscopy measurements show that the a-SEI contains minimal MgCO3, MgO, Mg(OH)2, and TFSI–, while being rich in MgCl2, MgF2, and MgS, when compared to the passivation layer formed on bare Mg in Mg(TFSI)2/DME.